LncRNA XIST promotes the progression of laryngeal squamous cell carcinoma via sponging miR-125b-5p to modulate TRIB2. Issue 4 (9th April 2020) - Liu, Chunxiu; Lu, Zhenjun; Liu, Hui; Zhuang, Shenfa; Guo, Ping
Abstract: Objective: X inactivate-specific transcript (XIST) is an attractive long noncoding RNA (lncRNA) functioning as an indicator of various human tumors, including laryngeal squamous cell carcinoma (LSCC). The present study was conducted to explore a novel regulatory network of lncRNA XIST in LSCC cells. Materials and methods: Quantitative real-time polymerase chain reaction (QRT-PCR) was used to detect the expression levels of XIST, miR-125b-5p and TRIB2 in LSCC cells and tissues. Cell proliferation, apoptosis, migration and invasion were detected by Cell Counting Kit-8 (CCK-8), flow cytometry and Transwell assays, separately. The relationship among XIST, miR-125b-5p and tribbles homolog 2 (TRIB2) was predicted by starBase v2.0 or TargetScan and confirmed by Dual-luciferase reporter assay. The TRIB2 protein expression was quantified by Western blot assay. Murine xenograft model was utilized to validate the role of XIST in vivo . Results: XIST was notably up-regulated in LSCC tissues and cells, and the high level of XIST was associated with the low survival rate of LSCC patients. XIST knockdown markedly repressed cell proliferation, migration and invasion and promoted the apoptosis of LSCC cells and the effects were antagonized by loss of miR-125b-5p. MiR-125b-5p was a target of XIST in LSCC cells, and it could bind to TRIB2 as well. Moreover, XIST-loss-induced down-regulation of TRIB2 could be significantly reversed by miR-125b-5p knockdown. XIST promoted the growth of LSCC tumor in vivo . Conclusion: LncRNA XIST promoted the malignance of LSCC cells partly through competitively binding to miR-125b-5p, which in turn increased TRIB2 expression.